Drug reaction with eosinophilia and systemic symptoms (DRESS): clinicopathological study of 45 cases. (9th September 2015) - Skowron, F.; Bensaid, B.; Balme, B.; Depaepe, L.; Kanitakis, J.; Nosbaum, A.; Maucort‐Boulch, D.; Bérard, F.; D'Incan, M.; Kardaun, S.H.; Nicolas, J.F.
Abstract Background Drug reaction with eosinophilia and systemic symptoms (DRESS) is a rare and severe adverse drug reaction. Large detailed studies of histopathological features of DRESS are sparse and suggest an association between keratinocyte damage and the severity of visceral involvement. Objectives To describe the dermatopathological features in a large series of DRESS and their possible association with clinical features and the severity of the disease. Methods A retrospective analysis of the clinicobiological and dermatopathological features in a monocentric cohort of patients with DRESS. Results From January 2005 to January 2013, 45 patients were validated as probable or definite cases of DRESS. The median age was 64 years (range 3–87). The most frequent clinical and biological features included: fever ≥38.5°C (95%), facial oedema (72%), enlarged lymph nodes (51%), visceral involvement (75%), blood eosinophilia (97%) and atypical lymphocytes (82%). Severe DRESS occurred in 24% and a fatal outcome in 6% of patients. Histopathological analysis showed that no specific histopathological pattern was characteristic for DRESS. However, several changes in different cutaneous compartments were observed in 2 of 3 of cases. Spongiosis (55%) and keratinocyte damage (53%) were the most common epidermal changes. Spongiosis was associated with non‐severe DRESS (P = 0.041) whereas confluent keratinocyte necrosis correlated with severe DRESS (P = 0.011). Vascular changes were frequent (88%). A moderate dermal perivascular lymphocytic infiltrate was invariably present, containing eosinophils, neutrophils and/or atypical lymphocytes in 57% of cases. Conclusions Epidermal changes are indicative for the severity of DRESS.